ANALISIS KESEHATAN DAN KESELAMATAN KERJA (K3) MENGGUNAKAN METODE HAZARD IDENTIFICATION AND RISK ASSESSMENT (HIRA) PADA BAGIAN SILO DI PT. SANTOSA UTAMA LESTARI MOYO - Iksan Adiasa; Nabilla; Arum Agrus Marsiwah; Bagas Afif Budianto (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
PT. Santosa Utama Lestari is a company that operates in the field of processing agricultural products, namely corn, which is located in Moyo Hilir District, Sumbawa Regency. As a company that operates in the field of processing agricultural products, of course there are risks that occur to PT workers. Santosa Utama Lestari, such as when moving corn, when carrying out machine repairs and so on. Based on the results of the hazard identification that has been carried out, there are 5 potential hazards at PT. Santosa Utama Lestari in the Corn Silo section. The potential dangers include dust and corn droppings in the silo, machines working on the silo, lots of material around the silo, and workers who often rush up the silo stairs, as well as workers who do not use Personal Protective Equipment (PPE) when climbing up. silos. The aim of conducting this research is to minimize the risk of work accidents occurring in the corn silo section at PT. Santosa Utama Lestari Moyo. The method used is Hazard Identification and Risk Assessment (HIRA). This research is expected to minimize the risk of work accidents in the silo section at PT. Santosa Utama Lestari Moyo so that workers can avoid work accidents.